Pengaruh Jamu Anemia terhadap Fungsi Ginjal di Rumah Riset Jamu“Hortus Medicus” Tawangmangu - Ardiyanto, Danang; Triyono, Agus; Nisa, Ulfatun (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2015)
The use of herbal medicine in the formal health care requires adequate scientific evidence especially on herbal safety data. The herb could be used for the treatment of anemia. The indicator for the safety of the herb was kidney function by measuring urea and creatinine. A clinical trial study with pre-post test designed was conducted at the Jamu Research Center